Intervals of Semen Collection from Boars during Early Reproductive Life: Evaluation of Seminal Fluid Parameters - Dornelles, Julianni; Rigon Rossi, Carlos Augusto; de Lima Schlösser, Luara Medianeira; Rech, Rodrigo Dalmina; Gräf, Cristian Guilherme; Melazzo de Andrade, Cínthia; Soares, Marcelo; Ceron, Marcos Speroni; Patias, Jovani (Acta Scientiae Veterinariae, 2019)
Background: In swine production, good reproduction rates can be achieved through genetic selection and reproductive biotechnologies. One of these biotechnologies is artificial insemination, which contributes to disseminate genes and optimize breeding boars, thus improving the quality of insemination doses. This study focused on evaluating the intervals between semen collection from boars at the beginning of their reproductive maturity vis-à-vis the viability of insemination doses. Materials, Methods & Results: Twenty 9-month-old boars of the genetic lineage AGPIC 337 (Agroceres PIC) were used in this study. The experimental design used here was completely randomized, and the randomly selected males were divided into four treatment groups, which were named according to the interval between semen sample collections: T1: 2 days; T2: 3 days; T3: 4 days and T4: 7 days. Each treatment comprised 5 animals, and at the end of the 90 days of this study, a total of 150 ejaculates were obtained in T1, 110 in T2, 90 in T3 and 60 in T4. The values of total motility, volume and sperm concentration of the ejaculates were evaluated, as was oxidative stress by means of thiobarbituric acid reactive substances (TBARS), the latter after 0, 72, 120 and 168 h of the study. Membrane integrity was evaluated at 0, 72, 120 and 168 h using the eosin-nigrosin staining procedure. Sperm heat resistance was tested after 120 h, and sperm morphology after 72, 120 and 168 h. Sperm concentrations differed, with T3 showing 27.04% and 29.65% higher concentrations (P < 0.05) than groups T2 and T1, respectively. Total motility in group T4 was 0.56%, 1.98% and 3.28% higher (P < 0.05) than in T3, T2 and T1, respectively, indicating that the 7-day interval produced the best result. The heat resistance test showed the expected results, i.e., T2 and T4 did not differ in terms of total motility, but that of T4 was 4.96% higher (P < 0.05) than T3 and 7.71% higher than T1. As for plasma membrane integrity, T4 had 6.45%, 8.09% and 12.72% more cells with intact membranes (P < 0.05) than T3, T2 and T1, respectively. With regard to TBARS, group T1 showed higher concentrations (P < 0.05) than T2 (6.18%), T3 (11.13%) and T4 (9.12%), i.e., the sperm cells in the animals of T1 showed greater changes. As for sperm morphology, the number of intact cells in T4 was 6.08%, 7.53% and 12.44% higher (P < 0.05) than in T3, T2 and T1, respectively. Discussion: With respect to total motility, other authors have reported similar results, i.e., the motility of sperm was highest when collected at 7-day intervals and lower when collected at shorter intervals. Despite the statistical differences between treatments, these results were found to be similar to those recommended in the literature for use in the preparation of insemination doses. Thus, we suggest that all the intervals between collections can be used in the routine of semen production centers, since the minimum requirement for an ejaculate to be accepted in an artificial insemination program is to have a total motility of no less than 70 percent. At the beginning of their reproductive maturity, boars may be subjected to intervals between collections of at least 2 days, without impairing the total motility of insemination doses. However, the best results are obtained when semen is collected at 7-day intervals, which ensures higher total motility, morphologically healthy cells with intact membranes, and less oxidative damage caused by lipid peroxidation.